Pro JavaFX 8 : a definitive guide to building desktop, mobile, and embedded Java Clients - Vos, Johan (Apress, 2014)
In Pro JavaFX 8 expert authors show you how to use the JavaFX platform to create rich-client Java applications. You'll discover how you can use this powerful Java-based UI platform, which is capable of handling large-scale data-driven business applications for PC as well as now mobile and embedded devices. Covering the JavaFX API, development tools, and best practices, this book provides code examples that explore the exciting new features provided with JavaFX 8 which comes as part of Oracle's new Java (SE) 8 release. This book also contains engaging tutorials that cover virtually every facet of JavaFX development and reference materials on JavaFX that augment the JavaFX API documentation. After reading and using this book, you'll have the authoritative knowledge that should give you an edge in your next JavaFX-based application projects for your job or your clients.